Elucidating the role of interleukin-17F in cutaneous T-cell lymphoma - Krejsgaard, Thorbjørn; Litvinov, Ivan V.; Wang, Yang; Xia, Lixin; Willerslev-Olsen, Andreas; Koralov, Sergei B.; Kopp, Katharina L.; Bonefeld, Charlotte M.; Wasik, Mariusz A.; Geisler, Carsten; Woetmann, Anders; Zhou, Youwen; et al. (Blood, 2013)
Inappropriately regulated expression of interleukin (IL)-17A is associated with the development of inflammatory diseases and cancer. However, little is known about the role of other IL-17 family members in carcinogenesis. Here, we show that a set of malignant T-cell lines established from patients with cutaneous T-cell lymphoma (CTCL) spontaneously secrete IL-17F and that inhibitors of Janus kinases and Signal transducer and activator of transcription 3 are able to block that secretion. Other malignant T-cell lines produce IL-17A but not IL-17F. Upon activation, however, some of the malignant T-cell lines are able to coexpress IL-17A and IL-17F, leading to formation of IL-17A/F heterodimers. Clinically, we demonstrate that IL-17F messenger RNA expression is significantly increased in CTCL skin lesions compared with healthy donors and patients with chronic dermatitis. IL-17A expression is also increased and a significant number of patients express high levels of both IL-17A and IL-17F. Concomitantly, we observed that the expression of the IL-17 receptor is significantly increased in CTCL skin lesions compared with control subjects. Importantly, analysis of a historic cohort of 60 CTCL patients indicates that IL-17F expression is associated with progressive disease. These findings implicate IL-17F in the pathogenesis of CTCL and suggest that IL-17 cytokines and their receptors may serve as therapeutic targets. •The Jak/Stat3 pathway promotes the expression of IL-17F in malignant CTCL cells.•IL-17F is highly expressed in a subset of CTCL patients and associated with progressive disease.